The Rise of Functional Categories. - Gelderen, Elly van (Linguistik aktuell, 1993)
In recent years, word order has come to be seen, within a Government Binding/Minimalist framework, as determined by functional as well as lexical categories. Within this framework, functional categories are often seen as present in every language without evidence being available in that language. This book contains arguments that even though Universal Grammar makes functional categories available, the language learner must decide whether or not to incorporate them in his or her grammar. For instance, it is shown that English has one (not two as often assumed) functional category between the co.